Alarm design for SCADA system of assembly cell-200 trainer - Zawawi, Mukmin (2008)
Alarm systems play a vital role in maintaining the safe operation in process plant. Moreover, the safety and efficiency of a plant's operation is assured by the usage of a reliable and user friendly alarm system. In this project, the main objective is to introduce an alarm feature inside the SCADA system. Identification of suitable guidelines in designing a good alarm system display is also part of the project's objective. Introduction of alarm feature inside the SCADA system is done by putting the Supervisory Control and Data Acquisition (SCADA) system to Assembly Cell-200 Trainer. Here, the SCADA system is equipped with an alarm system as the mean to monitor and control the trainer. The alarm design adopts the available alarm system guidelines as to figure out and judge the most suitable guidelines to be applied in this project. This exercise proves that general guidelines (e.g., use of an alarm philosophy) are essential in developing this projects. However, detailed guidelines (e.g., colour coding and symbol features) should be used more carefully and consistent to ensure the creation of understandable and recognizable display. From this project, a properly designed alarm system is developed, which provides the operators with enough information to prevent any abnormalities, fault conditions or undesired errors in the plant. This project also summarizes the principal guidelines to consider when designing and developing alarms in SCADA environment.